(3af GSJNOGe GdbHVIs - (3YHGS eMeO GMeOs ((3GdbGgQIs (3OGQ GdcJH GdYdejI ddfTQ h GdJhRjYs, 2002)
(3jhVM af GdLjJ chf Oh GdUMjM h ajg TQM eaUd dCOb GdJaGUjd GdehLhOI ajg, eOYe HUhQ JhVjMjI dHQhS dj faSg ddGbJQGH ef GdCOGA GdSdje dWQb GdgLhe h GdOaGY,ceG TQM eHGOFg h adSaJg aj gPg GdQjGVI(B.s